Clinical Analysis of Bloodstream Infection of Escherichia coli in Patients with Pancreatic Cancer from 2011 to 2019 - Changsen Bai; Xiuse Zhang; Dong Yang; Ding Li; Honglei Feng; Yueguo Li (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Pancreatic cancer patients were particularly predisposed to develop Escherichia coli (E. coli) bloodstream infection (BSI); however, little information is currently available. We set out to find E. coli BSI’s risk factors in pancreatic cancer to provide valuable experience. Methods. We retrospectively analyzed the clinical data of pancreatic cancer patients (31 cases with E. coli BSI and 93 cases without BSI) by a case-control study. SPSS 17.0 was adopted to perform univariate and multivariate analyses. Bacterial resistance analysis was performed by Whonet 5.6. Results. Hospitalization days ≥7 days, number of admissions ≥2 times, surgery, chemotherapy, the type of antibiotics used ≥2 species, albumin<40.0 g/L, and prealbumin < 0.2 g/L were the potential risk factors for pancreatic cancer patients with E. coli BSI (P<0.1). Multivariate logistic regression showed hospitalization days ≥7 days (OR = 11.196, 95% CI = 0.024–0.333, P<0.001), surgery (OR = 32.053, 95% CI = 0.007–0.137, P<0.001), and chemotherapy (OR = 6.174, 95% CI = 0.038–0.688, P=0.014) were the independent risk factors for E. coli BSI of pancreatic cancer patients. E. coli resistant to carbapenems was rare; they were susceptible to cephamycin and piperacillin/tazobactam. The 90-day mortality rate of the infected group was significantly higher than the control group (41.9% versus 8.6%, P<0.001). Conclusions. Hospitalization days ≥7 days, surgery, and chemotherapy are the independent risk factors for E. coli BSI of pancreatic cancer patients, which allows us to identify patients at potential risk and perform preventive treatment in time.